Analyzing and Mitigating Cyber Threats on Elecric Vehicles Chargers for Resilient Smart Grids - Abdelfatah, Ahmed (2024)
A Master of Science thesis in Electrical Engineering by Ahmed Abdelfatah entitled, “Analyzing and Mitigating Cyber Threats on Elecric Vehicles Chargers for Resilient Smart Grids”, submitted in April 2024. Thesis advisor is Dr. Mostafa Shaaban and thesis co-advisor is Dr. Abdelfatah Mohamed. Soft copy is available (Thesis, Completion Certificate, Approval Signatures, and AUS Archives Consent Form).